Lydia Jaeger and Herman Dooyeweerd: dialogues on the foundations of Christian scholarship - Coletto, Renato (Koers, 2015)
This article introduces and discusses Lydia Jaeger’s dialogue with and critical evaluation of a few aspects of Dooyeweerd’s philosophy. From her critical realist position, Jaeger evaluates Dooyeweerd’s rejection of the ‘Logos-speculation’ and his definitions of truth. As hedeviates from the Christian epistemological tradition referring to the ‘correspondence between thought and reality’, Jaeger argues that he fails to connect subject and object sufficiently. I arguethat in Dooyeweerd’s ontology subject and object are thoroughly interwoven by the law-order.I also question Jaeger’s critique that, in his epistemology, Dooyeweerd doesn’t make sufficient use of biblical resources and is too inclined towards idealism. I suggest that Jaeger’s contentions could be re-considered and that a more positive approach to reformational philosophy may open new avenues for her own research.This article introduces and discusses Lydia Jaeger’s dialogue with and critical evaluation of a few aspects of Dooyeweerd’s philosophy. From her critical realist position, Jaeger evaluates Dooyeweerd’s rejection of the ‘Logos-speculation’ and his definitions of truth. As hedeviates from the Christian epistemological tradition referring to the ‘correspondence between thought and reality’, Jaeger argues that he fails to connect subject and object sufficiently. I arguethat in Dooyeweerd’s ontology subject and object are thoroughly interwoven by the law-order.I also question Jaeger’s critique that, in his epistemology, Dooyeweerd doesn’t make sufficient use of biblical resources and is too inclined towards idealism. I suggest that Jaeger’s contentions could be re-considered and that a more positive approach to reformational philosophy may open new avenues for her own research.